Internalisasi Pendidikan Agama Islam dan KeMuhammadiyahan Bagi Santri Muallaf Di Pondok Pesantren Modern Muhammadiyah Boarding School (MBS) Banjarbaru Kalimantan Selatan - Fanani, Muhazir (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This study describes how the process of internalizing Islamic Education and KeMuhammadiyahn valeu for Muslim converts is carried out by the Modern Muhammadiyah Boarding School Boarding School Banjarbaru, South Kalimantan. This research also attempts to answer various existing problem formulations, including: (1) What are the efforts of the Banjarbaru MBS to convince converts to enter Islamic boarding schools? (2) How is the internalization of Islamic Religious Education and KeMuhammadiyahan Valeu implemented for Muslim converts at the Banjarbaru MBS? (3) What are the inhibiting and supporting factors in the internalization process? This study also aims to provide an informational description of the process of converting Islamic boarding students to the Modern Muhammadiyah Boarding School Boarding School Banjarbaru, South Kalimantan, then an overview of the various activities in the process of internalizing their Islamic religious education and KeMuhammadiyahan valeu as well as the things that become supporting and inhibiting factors in the process. The results of this study are expected to become media of information and study material for the Modern Muhammadiyah Boarding School Boarding School Banjarbaru, South Kalimantan in implementing Islamic education that is relevant for santri converts and as an addition to new scientific treasures for society in general.